Determining the region of origin of blood spatter patterns considering fluid dynamics and statistical uncertainties. (May 2019) - Attinger, Daniel; Comiskey, Patrick M.; Yarin, Alexander L.; Brabanter, Kris De
Highlights: A new method to improve the accuracy of a the Area of Origin determination is proposed This determination has traditionally involved an assumption of straight trajectories for spattered drops and has been without a solid basis for estimating an uncertainty in the resulting X, Y, Z coordinate estimates. This study aims to address the two above issues. The new method is based on fluid dynamics and on the propagation of statistical uncertainties. Spatter patterns used in this work are available in an open-access dataset, in high-resolution, so that other methods of reconstruction or stain selection can be compared with the one presented here. Abstract: Trajectory reconstruction in bloodstain pattern analysis is currently performed by assuming that blood drop trajectories are straight along directions inferred from stain inspection. Recently, several attempts have been made at reconstructing ballistic trajectories backwards, considering the effects of gravity and drag forces. Here, we propose a method to reconstruct the region of origin of impact blood spatter patterns that considers fluid dynamics and statistical uncertainties. The fluid dynamics relies on defining for each stain a range of physically possible trajectories, based on known physics of how drops deform, both in flight and upon slanted impact. Statistical uncertainties are estimated and propagated along the calculations, and a probabilistic approach is used to determine the region of origin as a volume most compatible with the backward trajectories. A publicly available data set of impact spatter patterns on a vertical wall with various impactor velocities and distances to target is used to test the model and evaluate its robustness, precision, and accuracy. Results show that the proposed method allows reconstruction of bloodletting events with distances between the wall and blood source larger than ∼1 m. The uncertainty of the method is determined, and its dependency on the distance between the blood source and the wall is characterized. Causes of error and uncertainty are discussed. The proposed method allows the consideration of stains indicating impact velocities that point downwards, which are typically not used for determining the height of the origin. Based on the proposed method, two practical recommendations on crime scene documentation are drawn.